The impact of ABLV case on harmonization of national bank insolvency laws and FOLTF assesment - Bambals, Kalvis (Riga Graduate School of Law, 2020)
ABLV case has brought about a strong response from the authorities, because it has highlighted the risk of legal uncertainty, when FOLTF banks don’t immediately get liquidated in accordance with SRB decision. The thesis examines the „limbo” phenomenon and its causes, and analyses the role of ABLV case in the context debate concerning the harmonisation of national bank insolvency frameworks. The main objectives of the Paper are to determine the practical EU resolution framework issues revealed by ABLV FOLTF cases and establish whether these issues can be dealt with without the harmonization tool.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Banking law